Macroeconomics and programming - Kurihara, Kenneth K. (London : Allen & Unwin, 1964)
This volume is intended to serve as a supplementary reading for the students of macroeconomic theory and mathematical programming. The volume is divided in two parts. Part 1. Macro Analysis and Policy. Part 2. Macro Linear Programming.
Includes index.
Includes bibliographical references: p. 94-95.
rpm 11/10/2017
Loans
Keywords: Macroeconomics